The Principal’s Leadership in Improving the Teachers Professional Competence at SMP Islam Singkil at Aceh Singkil Regency. - Abdil, Abdil; Murniati, Murniati; Niswanto, Niswanto (Jurnal Pendidikan Progresif, 2021)
The purpose of this study is to find out: the principal’s program, strategies program and obstacles faced by the principal in increasing teacher professional competence. This study uses descriptive method with qualitative approach. The subjects were principal, teachers and supervisor. The results showed that: 1) the principal’s program in enhancing the teachers professional competence by implementing discusion forum in the early school year together with vice principal curriculum section, the student affairs, facilities, teachers, committee, inspectors, and the discussion results are described in the school program. 2) The principal’s strategy in improving teacher professional competence creates a good climate, providing opportunities to every teacher to continue their education, rewarding outstanding teachers. 3) Supporting factors in solving obstacles such as: location of madrasas, giving fair assignments based on background of education, trust and support community, providing good opportunities in improving teacher professionalism, including teachers training, workshops, training, supporting teaching facilities and learning processes and transparent financial management as well. Keywords: leadership, principals, professional competence DOI: 10.23960/jpp.v11.i2.202119